Sustainability, Resilience, and Returns During COVID-19: Empirical Evidence from US and Indian Stock Markets. (June 2023) - Yadav, Neetu; Bhama, Vandana
The growing number of consulting reports published globally show mixed evidence of higher returns for environmental, social, and governance (ESG) indices as compared to equity indices. The present study analyzes whether or not sustainability provided resilience, during turbulent times, to the US and India, who were worst hit by the COVID-19 pandemic. The study tests whether higher ESG scores led to higher stock returns during and after the COVID-19 pandemic. The findings revealed little and negative associations of sustainability with stock returns for sample firms during the COVID-19 crisis. There is no empirical evidence indicating that sustainability guarantees resilience during crisis times. Investors have their own preference channels and taste for sustainability that are beyond their financial motives. JEL Codes: Q01, G120